Makna Keberkahan Rezeki Bagi Pengusaha Laundry Muslim (Studi Kasus di Lavender Laundry di Gubeng Kertajaya Surabaya) - Pradipta Aditya; Sri Herianingrum (Universitas Airlangga, 2015)
This descriptive study aims for describe the blessing in earning got by the laundry entrepreneur. There are four guidance that can be use to describe it. In addition, this study also describe the justified muamalah in Islam and the meaning of blessing in earning. The method used for collecting data was In-depth interview with the main informant and other informant that related with this study. Main informant in this research was the owner of Lavende Laundry. The result from this research showed that the blessing in earning can be earned by appy the religious theaching. Laundry entrepreneur got their blessed earning by applying the muamalah accordance to Islam. In the end, that blessed earning and muamalah brings in sincerity.